2021
DOI: 10.1002/ece3.7245
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted incubation: How dabbling ducks respond when flushed from the nest

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In this study, we found evidence that research disturbance negatively affects Great tit incubation behaviour. Our initial hypothesis was that females reacted to a disturbance event by staying away from the nest longer than expected given their incubation rhythms, but we also expected that this anti-predatory behaviour, observed in previous studies (Kovařík & Pavel, 2011; Ibáñez-Álamo & Soler, 2012; Croston et al, 2021; Tkaczyk et al, 2023), was compensated with longer on-bouts that ended up balancing any negative effect on nest attendance. However, we found that 1) the response of females was restricted to the ongoing (absent females) or first (present females) off-bout after a disturbance, i.e., a short recovery period; 2) females did not clearly compensate for their prolonged absence from the nest by lengthening subsequent on-bouts; and consequently, and despite the limited anti-predator response, 3) daily incubation rhythms were negatively affected by the disturbance events (i.e., lower nest attentiveness).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this study, we found evidence that research disturbance negatively affects Great tit incubation behaviour. Our initial hypothesis was that females reacted to a disturbance event by staying away from the nest longer than expected given their incubation rhythms, but we also expected that this anti-predatory behaviour, observed in previous studies (Kovařík & Pavel, 2011; Ibáñez-Álamo & Soler, 2012; Croston et al, 2021; Tkaczyk et al, 2023), was compensated with longer on-bouts that ended up balancing any negative effect on nest attendance. However, we found that 1) the response of females was restricted to the ongoing (absent females) or first (present females) off-bout after a disturbance, i.e., a short recovery period; 2) females did not clearly compensate for their prolonged absence from the nest by lengthening subsequent on-bouts; and consequently, and despite the limited anti-predator response, 3) daily incubation rhythms were negatively affected by the disturbance events (i.e., lower nest attentiveness).…”
Section: Discussionmentioning
confidence: 88%
“…Flushed females also stayed away from the nest longer if the researcher performed additional activities during a visit (e.g., measuring eggs), in contrast to absent females, which seemed unaffected by prolonged visits. Experiments simulating the presence of predators near the nest generally result in incubating females leaving the nest for longer periods (Kovařík & Pavel, 2011; Ibáñez-Álamo & Soler, 2012; Croston et al, 2021; Tkaczyk et al, 2023), although the duration and magnitude of the response is species-specific (Ghalambor & Martin, 2002; Zanette et al, 2011; Ghalambor et al, 2013) and/or dependent on predator type (Basso & Richner, 2015a). Absent females appeared to evaluate the disturbance caused by the researchers differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we detected no relationship between space use and infection in mallards, which were sampled during the breeding season. Breeding‐season movements are constrained by nesting behavior, especially for females (Croston et al, 2021; Eichholz & Elmberg, 2014), so infection might have limited effects on movement during the summer. Local processes are among the most important drivers of large‐scale patterns of influenza infection in wild waterfowl (Gorsich et al, 2021), and longer waterfowl residence times are associated with influenza outbreaks in poultry (Humphreys et al, 2020); therefore, these results indicate that any infection‐related reductions in local movements could affect both local and large‐scale viral dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after clutch completion, mallard (Anas platyrhynchos) and gadwall (Mareca strepera) average 1.7 and 1.4 incubation recesses per day, respectively, and these recesses last on average, 91-193 minutes depending on the species and the time of day [18]. Previous research has demonstrated that dabbling duck hen nest attendance and incubation rhythms can be influenced by a wide variety of factors including ambient temperature, time of day, date, nest age, food availability and nutrient limitation, hen body condition, predation risk, disturbance, and weather [16,[18][19][20][21][22][23]. Thus, incubating hens appear to be responsive to changing physiological and environmental conditions and moderate their incubation behavior accordingly.…”
Section: Introductionmentioning
confidence: 99%